Genome-wide analysis reveals the MORC3-mediated repression of PD-L1 expression in head and neck cancer - Fu, Wenxuan; Chang, Xiaomeng; Ye, Kun; Zheng, Zige; Lai, Qianyi; Ge, Minyang; Shi, Yan (Frontiers in Cell and Developmental Biology, 2024)
Introduction Programmed death-ligand 1 (PD-L1) plays essential roles in the negative regulation of anti-tumor immunity. However, the regulatory mechanisms of PD-L1 expression need further exploration. MORC family CW-type zinc finger 3 (MORC3) is a transcriptional factor that regulates innate immune responses, but the expression and roles of MORC3 in cancers remain largely unknown. The present study explored the expression of MORC3 in cancers at both transcriptional and translational levels. Methods The target genes and pathways were analyzed using RNA interference (RNAi), RNA sequencing (RNA-seq), and quantitative real-time polymerase chain reaction (qRT-PCR) technology in head and neck cancer cells. The expression of MORC3 and its target genes were also analyzed in single cancer cells. Results MORC3 was significantly downregulated in multiple cancers, including head and neck cancer, and low expression of MORC3 was associated with poor overall survival. MORC3 knockdown significantly increased the expression of many immune-related genes, including interferon (IFN)-associated genes [MX dynamin like GTPase 2 (MX2), interferon induced protein with tetratricopeptide repeats 1 (IFIT1), interferon induced protein with tetratricopeptide repeats 2 (IFIT2), interferon regulatory factor 7 (IRF7), interferon regulatory factor 9 (IRF9), interferon induced protein 44 like (IFI44L), interferon induced transmembrane protein 1 (IFITM1), interferon induced transmembrane protein 3 (IFITM3), interferon induced protein 44 (IFI44), and interferon induced with helicase C domain 1 (IFIH1)]. MORC3 knockdown significantly upregulated PD-L1 and signal transducer and activator of transcription 1 (STAT1) expression. Moreover, the LINC00880 immune-related long non-coding RNA (lnc-RNA) was upregulated by MORC3 knockdown. Silencing LINC00880 attenuated PD-L1 expression. MORC3 knockdown also increased the expression of cellular proliferation-related genes and promoted cancer cell proliferation. Conclusion The present study demonstrated that MORC3 regulates IFN-associated pathways and is a novel repressor of PD-L1 expression and cancer cell proliferation.